ANALYSIS OF CUSTOMER BEHAVIOR USING THE APRIORI METHOD - Septiano, Renil; Defit, Sarjon; Sari, Laynita (Dinasti Publisher, 2021)
Data is a very valuable asset because it is able to provide accurate, easy and fast information. This study processes coffee shop business data in the city of Padang to determine how customers behave in choosing menus. From the results of data processing. Researchers processed the data using the a priori method. From the results of data processing at a support value of 15%, it is found that the majority of customers still buy menus in units.